Real‑world Outcomes and Predictors of Vision Loss after Panretinal Photocoagulation for Diabetic Retinopathy: Five‑year Follow‑up - Taufaeteau, Antonio; Bhatta, Subash; Pant, Nayana; Lopez, Valeria; Sikivou, Biu; Qoqonokana, Mundi; Naviri, Varanisese (Nepalese Journal of Ophthalmology, 2026)
Introduction: Diabetic retinopathy is a leading cause of vision loss in Fiji, where treatment options beyond panretinal photocoagulation (PRP) remain limited. In this context, evaluating longterm outcomes of PRP can provide critical insights in patient management. Objective: To evaluate real-world long-term outcomes and predictors of vision loss following PRP for severe nonproliferative diabetic retinopathy (NPDR) and proliferative diabetic retinopathy (PDR) in a resource-constrained setting. Methodology: Retrospective study was done using five-year follow-up data of eyes treated exclusively with PRP at the Pacific Eye Institute, Fiji, between January 2010 and December 2015. Patients with advanced PDR, coexisting retinal pathology, or adjunctive therapies were excluded. Visual acuity, retinopathy grading, and systemic factors were assessed. Statistical analyses included Chi-square tests, independent samples t-tests, and generalised estimating equations. Result: A total of 516 eyes (91 NPDR, 425 PDR) from 283 patients were included. At five years, 68% of PDR eyes achieved stability, 19% remained active, and 13% progressed to advanced PDR. Among NPDR eyes, 17.6% progressed to active PDR and 7.7% to advanced PDR. The difference in progression between NPDR and PDR eyes was significant at two years (p <0.001) but not at five years (p =0.317). Overall, eyes lost 2.7 lines of logMAR visual acuity; NPDR eyes lost more vision (3.9 lines) from baseline than PDR eyes (2.5 lines, p=0.059). Poor glycaemic control, older age, and unstable retinopathy were significant predictors of vision loss (p ≤0.01). Conclusion: Panretinal photocoagulation remains essential for managing PDR, achieving longterm stability in most eyes. In severe NPDR, however, its use requires careful risk–benefit assessment. Importantly, access to intravitreal antiVEGF injections and vitrectomy should also be globally prioritised, as many eyes progress to advanced PDR and experience vision loss in the absence of adjuvant therapy despite laser treatment.